2002
DOI: 10.1080/00207450290025905
|View full text |Cite
|
Sign up to set email alerts
|

Brief Communication HUMAN SCALP RECORDED SIGMA ACTIVITY IS MODULATED BY SLOW EEG OSCILLATIONS DURING DEEP SLEEP

Abstract: The EEG during deep sleep exhibits a distinct cortically generated slow oscillation of around and below 1 Hz which can be distinguished from other delta (0.5-3.5 Hz) activity. Intracranial studies showed that this slow oscillation triggers and groups cortical network firing. In the present study, we examined whether the phases of the slow oscillation during sleep stage 4 are correlated with the magnitude of sigma (12-16 Hz) and gamma (> 20 Hz) scalp activity. For this purpose, 10-min segments of uninterrupted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 16 publications
2
8
0
1
Order By: Relevance
“…In most of the cases, gamma oscillations were correlated with positive peaks of scalp slow waves, confirming previous animal data suggesting that gamma oscillations occur during the active component of the slow wave (‘UP’ state). This observation of enhanced gamma activities during surface-positive components of slow oscillations is also consistent with the grouping of spindle and beta activities reported for human scalp EEG [13], [14]. This depolarization phase is associated with increased cortical firing, which drives the generation of spindle, beta and gamma oscillations in thalamo-cortical feedback loops [3].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In most of the cases, gamma oscillations were correlated with positive peaks of scalp slow waves, confirming previous animal data suggesting that gamma oscillations occur during the active component of the slow wave (‘UP’ state). This observation of enhanced gamma activities during surface-positive components of slow oscillations is also consistent with the grouping of spindle and beta activities reported for human scalp EEG [13], [14]. This depolarization phase is associated with increased cortical firing, which drives the generation of spindle, beta and gamma oscillations in thalamo-cortical feedback loops [3].…”
Section: Discussionsupporting
confidence: 89%
“…Nevertheless, although activities in the gamma-range have been observed at the scalp level during a variety of cognitive tasks [12], no evidences of a phasic expression of gamma activities during SWS in human macroscopic EEG recordings were reported so far. For example, Fell and colleagues [13] used the scalp EEG data during sleep and showed that sigma activity (12–16 Hz) is modulated by slow EEG oscillations. In another study, Molle and collaborators [14] found that grouping of spindles and beta oscillations are coincident with slow waves in human SWS.…”
Section: Introductionmentioning
confidence: 99%
“…9(c2)), results are not very good for f-indexes greater than 2.5 or less than 0.5 Hz. More precisely saying, an f-index, which is greater than 2.5 Hz, fails to give low standard deviation in light and deep anesthesia (stages 1,4,5), and an f-index which is less than 0.5 Hz, basically fails to yield a low standard deviation in deep and moderate anesthesia (stages 1 to 3). Fig.…”
Section: Different Delta Sub-bands and Their Relating Pom: Applicatiomentioning
confidence: 95%
“…The depolarizing phase, on the other hand, is found to be accompanied by a corticothalamic facilitation of neural firing. Fell et al, used the scalp EEG data during sleep and showed that sigma activity ( [12][13][14][15][16] Hz) is modulated by slow EEG oscillations [5]. However, they did not find a strong modulation between slow delta waves and gamma oscillations on scalp EEG recordings as Steriade et al, had shown in their neuronal level recordings.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation